Learning Opportunities in Postgraduate Training Programmes - Almoallim, Hani (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2008)
Postgraduate training programmes need to have critical internal review process. An evidence-based review on morning clinic reports, lectures in postgraduate training programmes, outpatient clinics and journal clubs is presented.